Fabrication of PεCL–AuNP–BSA core–shell–corona nanoparticles for flexible spatiotemporal drug delivery and SERS detection. (14th May 2021) - Hong, Yanhang; Ju, Yuanyuan; Chen, Wenjuan; Liu, Yingze; Zhang, Mingming; Zhao, Hanying
Abstract : PεCL–AuNP–BSA core–shell–corona nanoparticles for spatiotemporal drug delivery and SERS detection. Abstract : Nanoparticles with protein coronae can be used as promising multifunctional platforms for nanomedicine due to the possibility of performing surface functionalization on protein molecules and the achievement of biomedical properties. In this research, nanoparticles (NPs) with poly(ε-caprolactone) (PεCL) cores, gold NP (AuNP) shells and BSA coronae were fabricated by a self-assembly approach. The hydrophobic PεCL cores were used to encapsulate curcumin (CUR), the AuNP shells were decorated with a Raman probe, and the protein molecules in the coronae were functionalized with folic acid (FA). The self-assembly behaviors, drug delivery and the surface-enhanced Raman scattering (SERS) effect of the hybrid NPs were investigated in this research. The sizes of the core–shell–corona NPs (CSCNPs) are dependent on the initial concentrations of PεCL and AuNPs. The CUR in CSCNPs show enzyme-triggered release properties. The added lipase or trypsin can facilitate the CUR release from the hybrid NPs. The functionalization of CSCNPs with FA can significantly improve the internalization of NPs into 4T1 tumor cells due to the overexpressed folate receptors on the cells. In addition, the SERS effect of CSCNPs can be achieved when the AuNPs are decorated with 2-naphthalenethiol. The hybrid CSCNPs can be used as a promising platform for spatiotemporal drug delivery, cell imaging, and theranostics. Based on the same CSCNP platform, flexible functions can be adjusted according to the application needs.